Enhancing an International Experience for Students through Reflective Writing Exercises and Self-Directed Learning - Kerry K. Fierke; Karen Bastianelli; Lisa Vogelsang; Ladona Tornabene; Gardner A. Lepp (Arizona State University, 2016)
The article identifies a student-centered approach to generating meaningful learning outcomes in a study-abroad program.  It details how Reflective Writing Exercises (RWE) were incorporated into a course involving international travel. A group of students in a short-term study abroad course was subject to a specific reflective writing process designed to limit the potential cultural and logistic obstacles of the travel experience, and enhance the students' overall experience. This process included three distinct reflective writing periods: prior to travelling, during the trip, and after the trip. The RWEs required the students to think deeply and take partial ownership of the quality of their learning experiences through a self-directed learning component while abroad. Qualitative data collection revealed that students benefited from the overall reflective writing experience. The evaluated effects of the student-selected activities that emerged from the RWEs, and how other instructors may incorporate RWEs for study abroad, are also discussed.